Vitamin D attenuates endothelial dysfunction in streptozotocin induced diabetic rats by reducing oxidative stress. (4th July 2022) - Said, Mona A.
Abstract: Diabetes mellitus (DM) is associated with micro- and macrovascular complications and increased cardiovascular risk. Vitamin D deficiency is the most common nutrient deficiency in the world. This study aimed to examine the effects of diabetes on the endothelial function and the role of vitamin D supplementation. Male Wistar rats ( n  = 30) were randomly assigned to three groups; control untreated, diabetic untreated, and diabetic groups treated with vitamin D at a dose of 12.5 μg/kg body weight, dissolved in 0.3 ml olive oil orally for 10 weeks. Compared to the control group, the serum glucose, serum asymmetric dimethylarginine (ADMA), aortic malondialdehyde (MDA) levels, endothelin-1 (ET-1) level, inducible nitric oxide synthase (iNOS) activity in diabetic rats were increased, whereas aortic superoxide dismutase (SOD) activity, nitric oxide (NO) levels, and constitutive NOS (cNOS) activity were decreased. Administration of vitamin D to diabetic rats resulted in a decrease of serum glucose, serum ADMA, a decrease of aortic MDA levels, ET-1 and iNOS activity, an increase of aortic SOD activity, NO levels, and cNOS activity. Vitamin D administration attenuated diabetic induced endothelial dysfunction by reducing oxidative stress. These results indicate that chronic vitamin D treatment might be useful in preventing diabetic vascular complications associated with endothelial dysfunction.